Norway's Millennium of Christianity and Decade of Celebration - Kjølsvik, Idar (Lutheran quarterly, 2020)
The Church of Norway and the Kingdom of Norway are celebrating a millennium of Christianity, a span that includes the first Christians in North America. Therefore, Norwegians and others are about to start a decade of celebrating and discussing Christian, Lutheran, and national identity for a new millennium. Specifically, Norway is focusing on July 29, 2030, as the anniversary, celebrating one Christian millennium in order to prepare for a new and different one. This essay catalogs the places, events, and significance of the observances.